2019
DOI: 10.1021/acs.est.8b07303
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Species Sorting and Immigration on the Bacterial Assembly of Different-Sized Aggregates in a Full-Scale Aerobic Granular Sludge Plant

Abstract: In aerobic granular sludge (AGS) systems, different-sized microbial aggregates having different solids retention time (SRT) coexist in the same reactor compartment and are subjected to the same influent wastewater. Thus, the AGS system provides a unique ecosystem to study the importance of local (species sorting) and regional (immigration) processes in bacterial community assembly. The microbial communities of different-sized aggregates (flocs <0.2 mm, small granules (0.2–1.0 mm) and large granules >1.0 mm), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
80
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 62 publications
8
80
1
Order By: Relevance
“…Biofilms can establish emerging features not always possible outside the biofilm environment, such as nutrient gradients across trophic groups and aerobic or anaerobic microniches ( 2 ). Classical models of formation and growth of attached biofilms are widely accepted ( 1 , 3 ), but biofilm development and community assembly by complex microbiomes is still of increasing interest ( 4 8 ). A challenge for such studies is in identifying highly replicated, complex, and diverse communities that experience identical environmental conditions, especially at scales relevant to cells ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofilms can establish emerging features not always possible outside the biofilm environment, such as nutrient gradients across trophic groups and aerobic or anaerobic microniches ( 2 ). Classical models of formation and growth of attached biofilms are widely accepted ( 1 , 3 ), but biofilm development and community assembly by complex microbiomes is still of increasing interest ( 4 8 ). A challenge for such studies is in identifying highly replicated, complex, and diverse communities that experience identical environmental conditions, especially at scales relevant to cells ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms can establish emerging features not always possible outside the biofilm environment, such as nutrient gradients across trophic groups and aerobic or anaerobic microniches (2). Classical models of formation and growth of attached biofilms are widely accepted (1,3), but biofilm development and community assembly by complex microbiomes is still of increasing interest (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Island biogeography theory is one of the most influential paradigms in ecology, which is central to several disciplines (e.g., conservation ecology and metapopulation theory) and continues to provide insights into research of island-like systems [41][42][43][44]. For example, Ali, Wang, Salam, Hari, Pronk, Van Loosdrecht, Saikaly [44] observed that the species sorting was significantly higher in flocs and small granules than large granules in aerobic granular sludge system, while putative functional populations were enriched with an increase in microbial aggregates size. Here, we adopted the theory of island biogeography as a conceptual framework for understanding the microbial ecology of microbes within a granule-based PN/A bioreactor.…”
Section: Granular Aggregate As a Microscopic Model System For Island mentioning
confidence: 99%
“…Therefore, we hypothesized granules with different sizes represent microscopic islands with different island areas, thus affecting microbial diversity and functional diversity [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Intense interest now surrounds the study of granular biofilms as playgrounds to investigate fundamental concepts in microbial ecology (19). Recent studies (20, 21) have used granules – albeit aerobic, and not anaerobic, granules – to study the roles of phenomena, such as immigration and species sorting, driving microbial community assembly.…”
Section: Introductionmentioning
confidence: 99%